Prevalence of Congenital Cutaneous Anomalies in 1000 Newborns and a Review of the Literature - Solak, Sezgi Sarikaya; Altunay, Ilknur Kivanc; Demirci, Gulsen Tukenmez; Can, Burce (American Journal of Perinatology, 2016)
Objective There are limited reports studying on congenital cutaneous anomalies in newborns, particularly in Turkey. Some of congenital cutaneous anomalies serve as an important clue for accompanying syndromes or other medical conditions. This study aimed to determine the prevalence of congenital cutaneous anomalies in newborns and to discuss their clinical significance with a brief review of literature.Study Design A total of 1,000 newborns were examined by a dermatologist in a hospital-based, cross-sectional, prospective study between October 2011 and April 2012.Results We observed 11 different congenital cutaneous anomalies in 48 newborns of 1,000 (4.8%). The most commonly seen anomalies were sacral dimple, accessory nipple, acrochordon, hypospadias, open spinal dysraphism, and accessory tragus. None of the newborns with cutaneous anomalies had any association.Conclusions Although congenital cutaneous anomalies are rare in newborns, clinicians should be aware of them as they may be in association with syndromes and other medical conditions. It is also important to give appropriately provided information to avoid parents concerns.
Keywords: newborn; cutaneous anomalies; sacral dimple; accessory nipple; accessory tragus